Screening of Plant Extracts used in Traditional Antidiarrhoeal Medicines against Pathogenic Escherichia coli - Patel, Jayshree D; Patel, Devang K; Shrivastava, Anshu; Kumar, Vipin (Scientific World, 2010)
The petroleum ether, chloroform, methanol and aqueous extracts of Acacia catechu L. f. (bark), Acacia nilotica L. (bark), Aegle marmelos L. Correa. (fruit) Azadirachta indica L. (leaves), Annona squamosa L. (leaves), Trachyspermum ammi L. (seeds), Holarrhena antidysenterica L. (bark) and Ocimum basilicum L. (leaves) were tested against Enteropathogenic Escherichia coli (EPEC). These are the plants traditionally used by rural populace of semi arid regions of India for the treatment of diarrhoea. The ethnopharmacological information on the plants was collected by interviewing the traditional healers, community leaders and rural people of Gujarat State. The agar-well diffusion assay method was used to access the activities of plant extracts against the test organism. The results obtained show the strong activity of petroleum ether extract of A. marmelos, A. indica, T. ammi and H. antidysenterica; chloroform extract of A. catechu, A. indica and T. ammi; and methanol extract of A. catechu, A. nilotica, A. marmelos and T. ammi (MIC, d" 50 ì g/ml) followed by petroleum ether extract of O. basilicum and chloroform extract of A. nilotica, A. marmelos and H. antidysenterica (MIC, 50-100 ì g/ml). These preliminary results will be helpful in rationalizing the use of plants based traditional medicines in modern systems of health care. Key words: Medicinal plants; Herbal extracts; Traditional medicines; Escherichia coli. DOI: 10.3126/sw.v6i6.2636 Scientific World, Vol. 6, No. 6, July 2008 63-67